Economic Convergence Study in the Eastern Region of Indonesia 2018-2022 - Dara Julia Asmara Dita; Wiwin Priana Primadhana; Wirya Wardaya (International Journal of Economics, Business and Innovation Research, 2024)
Economic growth and convergence are defined as economic indicators that can characterize the extent of the difference or gap between developed and developing countries. The purpose of this study was to determine the convergence of sigma, absolute convergence, conditional convergence, the influence of HDI investment, and labor on the convergence of economic growth between provinces in the Eastern Region of Indonesia and to find out how much convergence speed is produced every year. The research was conducted in 17 provinces in the Eastern Region of Indonesia as an analysis unit. from 2018-2022. The data used is a panel, with analysis tools namely sigma convergence, beta convergence, and panel data regression using the FEM model. The results of sigma convergence, absolute beta convergence, and conditional beta convergence research show that there is a convergence of economic growth. Based on the results of the conditional beta convergence estimation, the human development index (HDI) has a positive and significant effect on economic growth. The speed of convergence with the absolute convergence analysis method, it was found that the time required to achieve a half steady state was 10.2 years and the growth to be achieved was 6.8 percent per year. Meanwhile, with the conditional convergence analysis method, it was found that the time needed to move towards a half-steady-state is 140.4 years and the economic growth that must be achieved is 0.5 percent per year.